Giải các phương trình sau :
a) \(2\sin^2x+\sin x\cos x-3\cos^2x=0\)
b) \(3\sin^2-4\sin x\cos x+5\cos^2x=2\)
c) \(\sin^2x+\sin2x-2\cos^2+5\cos^2x=2\)
d) \(2\cos^2x-3\sqrt{3}\sin2x-4\sin^2x=-4\)
Giải các phương trình sau :
a) \(\sin^2\dfrac{x}{2}-2\cos\dfrac{x}{2}+2=0\)
b) \(8\cos^2x+2\sin x-7=0\)
c) \(2\tan^2c+3\tan x+1=0\)
d) \(\tan x-2\cos x+1=0\)
Giải các phương trình sau:
1) tan x + tan 2x + tan 3x = 0
2) cos 2x. cos 4x = \(\frac{\text{1}}{\text{2}}\)
3) cot x - tan x = cos x - sin x
4) 4sin x. sin 2x. sin 4x = sin 3x
Giải phương trình sau: \(\cot x-1=\dfrac{\cos2x}{1+\tan x}+\sin^2x-\dfrac{1}{2}\sin2x\)
Giải các phương trình sau :
a) \(\cos^2x+2\sin x\cos x+5\sin^2x=2\)
b) \(3\cos^2x-2\sin2x+\sin^2x=1\)
c) \(4\cos^2x-3\sin x\cos x+3\sin^2x=1\)
Giải các phương trình sau
a) \(sin^6x+cos^6x=cos2x+\dfrac{1}{16}\)
b) \(sin^4\dfrac{x}{2}+cos^4\dfrac{x}{2}=\dfrac{5}{2}-2sinx\)
c) \(cos5xcosx=cos4xcos2x+4-3sin^2x\)
d) \(2cosxcos2x=1+cos2x+cos3x\)
e) \(sin3x+cos2x=2\left(sin2xcosx-1\right)\)
Giải các phương trình sau
1) sin3x = 0
2) cos25x = 0
3) tan (x - 15o) = 3tan (x + 15o)
4) cos x + cos 2x + cos 3x = 0
5) sin 2x + sin 4x + sin 6x = 0
6) tan x + tan 2x + tan x.tan 2x = 1
7) tan x + tan 2x + tan 3x = tan x.tan 2x.tan 3x
8) cot2x + \(\frac{\text{3}}{\text{sin x}}\) + 3 = 0
Giải các phương trình sau :
a) \(3\cos^2x-2\sin x+2=0\)
b) \(5\sin^2x+3\cos x+3=0\)
c) \(\sin^6x+\cos^6x=4\cos^22x\)
d) \(-\dfrac{1}{4}+\sin^2x=\cos^4x\)
a, cos4x + 12sin2x -1 = 0
b, cos4x - sin4x + cos4x = 0
c, 5.(sinx + \(\dfrac{cos3x+sin3x}{1+2sin2x}\) ) = 3 + cos2x với mọi x\(\in\left(0;2\pi\right)\)
d, \(\dfrac{sin3x}{3}=\dfrac{sin5x}{5}\)
e, \(\dfrac{sin5x}{5sinx}=1\)
f, cos23x - cos2x - cos2x =0
g, cos4x + sin4x + cos(\(x-\dfrac{\pi}{4}\) ) . sin(\(3x-\dfrac{\pi}{4}\) ) - \(\dfrac{3}{2}\) = 0
h, sin\(\left(2x+\dfrac{5\pi}{2}\right)\) - 3cos\(\left(x-\dfrac{7\pi}{2}\right)\)= 1 + 2sinx với x\(\in\left(\dfrac{\pi}{2};2\pi\right)\)
i, 5sinx - 2 = 3.( 1- sinx ) . tan3x
k, ( sin2x + \(\sqrt{3}cos2x\))2 - 5 = cos \(\left(2x-\dfrac{\pi}{6}\right)\)
l, \(\dfrac{2.\left(cos^6x+sin^6x\right)-sinx.cosx}{\sqrt{2}-2sinx}=0\)
m, \(\dfrac{\left(1+sinx+cos2x\right).sin\left(x+\dfrac{\pi}{4}\right)}{1+tanx}=\dfrac{1}{\sqrt{2}}cosx\)
Mọi người giúp mình nha ! Mình cần gấp cho ngày mai